Contribution of Teachers' Pedagogical Competencies and Professional Competencies to Classroom Management - Handini, Oktiana (Research Horizon, 2024)
This research aims to evaluate the contribution of pedagogical competence and professional competence to classroom management in the Independent Curriculum Independent Curriculum. Primary data was obtained through a questionnaire. Analysis techniques include validity tests, regression analysis, t test, F test, coefficient of determination, and classical assumption analysis. The results show that pedagogical competence significantly contributes positively to classroom management in the independent curriculum. Likewise with professional competence. Both together have a significant contribution to classroom management in an independent curriculum. The F test results show that these two variables together contribute significantly to classroom management. The proportion of influence of the two variables on classroom management is 95.7%, while the remainder is influenced by other variables. The classical assumption test shows that this multiple linear regression model meets the normality assumption and is free from classical assumptions. This research confirms the importance of pedagogical competence and professional competence in supporting effective classroom management in the context of an independent curriculum.